Eco-functional intensification through natural and organic farming of groundnut (Arachis hypogaea) - H K, VEERANNA; H D, SHILPA; M E, SHILPA; S K, ADARSHA; CHITTARAGI, AMOGHAVARSHA; T G, Amrutha (The Indian Journal of Agricultural Sciences, 2026)
The primary challenge for sustainable intensification of agriculture is to increase food and feed production while minimising greenhouse gas emissions, biodiversity loss and nutrient leaching. The experiment was conducted during winter (rabi) seasons of 2019–20 and 2020–21 at Zonal Agricultural and Horticultural Research Station, Keladi Shivappa Nayaka University of Agricultural and Horticultural Sciences, Navile, Shivamogga, Karnataka to compare different farming systems, i.e. natural farming (NF), organic farming (OF), conventional farming (CF) and farmer practices (FP) in groundnut (Arachis hypogaea L.). The results revealed that conventional farming recorded significantly higher pod yield, pod weight/plant, and shelling percentage compared to natural and organic farming systems. The number of pods/plant under natural farming was statistically comparable to conventional farming; however, this did not translate into higher pod yield. Haulm yield was significantly higher under natural farming, however, the organic carbon and micronutrients were significantly higher in the OF. Higher amounts of major and secondary nutrients were recorded in the CF, followed by OF. However, higher soil microbial activity was observed in NF which was comparable to OF. Pod yield was significantly lower in NF and OF; while, soil nutrient levels and soil microbial activity were higher. Practicing OF and NF over a long period could reduce the yield gap. Both natural and organic farming increase soil organic carbon and improve the stability of soil abiotic and biotic characteristics and they are expected to play important roles in long-term sustainable agriculture.